Вы находитесь на странице: 1из 14

1.

Df. , n. , n.
Pn = n!
C {1, 2, 3, . . . , n}. ,
, n. , n ,
(n 1) , (n 2) .. ,
n(n 1)(n 2) . . . 1 = n! B
C n n, Ann = n!/(n
n)! = n! B
2.

Df. , k
n.
Akn =

n!
(n k)!

C {1, 2, 3, . . . , n}, k
. n ,
(n 1) , k- (n k + 1) . ,
n(n 1)(n 2) . . . (n k + 1) = n!/(n k)! B
3.

Df. , k
n.
Cnk =

n!
k!(n k)!

C n k n!/(n k)!. k
, , Pk = k! .

,
n k k : Akn /Pk B
4.

Df.
: (a + b)n .
n

(a + b) =

n
X

Cnk ank bk

(n Z+ )

k=0

Cnk , n k, .
n
( 1, 1 1,
, ; n- k-
( ) Cnk ).
1
1
1
1
1
1

2
3

4
5

1
1
3
6

10

1
4

10

1
5

, (a + b)4 = a4 + 4a3 b + 6a2 b2 + 4ab3 = b4 .


C (a + b)n , (a + b) n .
(a + b)(a + b) . . . (a + b). , an 1. ,
ank bk , a (nk) , b k .
Cnnk = Cnk , , ank bk Cnk B
5. ,

Df. z = x + iy,
Re = x, Im = y. x ,
, Re, p
y
Im. |z| = x2 + y 2 ( . )
, .
Arg z ( ) z
Re - . :

arctg
I IV

b
= + arctg
II

+ arctg b III
a

Df. z = |z|(cos + i sin ).


Df. z = |z|ei .
, :
ei = cos + i sin
C , ( x0 = 0) :
ex = 1 + x +

x2 x3
+ + ...
2! 3!

cos x = 1

x2 x4 x6
+ + ...
2! 4!
6!

sin x = x

x3 x5 x7
+ + ...
3! 5!
7!

:
eix = 1 + ix

x2 ix3 x4 ix5

+ +
+ ...
2!
3!
4!
5!

i sin x = ix

ix3 ix5 ix7


+

+ ...
3!
5!
7!

, eix = cos x + i sin x B


6. 2- 3- . ()

Df. n- K, n n K,
.
n ,
3

( , , n!),
(1) , j,
i.
2-
: a11 a22 a12 a21 . ,
(a11 , a12 ) (a21 , a22 ).
3- . a = (a11 , a12 , a13 ), b = (a21 , a22 , a23 )
c = (a31 , a32 , a33 ) , , , .
(). i
:
det A =

n
X

aik Aik

k=1

aij ( Aij ) (1)i+j


Mij , , i- j- .
C k- n :


a1k
a1k
0
0
0
a2k 0 a2k 0
0


a3k = 0 + 0 + a3k + . . . + 0


. . . . . . . . . . . .
. . .
ank
0
0
0
ank
, , det A n , . n-
ank Ank , , () B
7. 2- 3-

Df. ,
,
.
. :

a11 x + a12 y + a13 z = b1


a21 x + a22 y + a23 z = b2

a31 x + a32 y + a33 z = b3


4



a11

= a21
a31

:

a12 a13
a22 a23
a32 a33

, (x, y z) , ,
, :






b1 b2 b3
a11 a12 a13
a11 a12 a13






x = a21 a22 a23 y = b1 b2 b3 z = a21 a22 a23
a31 a32 a33
a31 a32 a33
b1 b2 b3
!
x y z
, ,
:

18. ;

) z = 1 + i 3
r
 2
2
|z| = (1) +
3 =2

3 (II .)
2
= =
= + arctg
1
3
3
2
2
2
z = 2(cos
+ i sin ) = 2ei 3
3
3
) z = cos

i sin
3
3

I . cos i sin = cos () + i sin () (


).
!
!

cos i sin = cos


+ i sin
3
3
3
3
|z| = 1,

z = ei 3

II . , ,
.

1
3
cos i sin = i
3
3 2
2
5

s
|z| =

1 3
+ =1
4 4

3



2 = arctg 3 (IV=.)
= arctg
3
1
2
!
!

z = cos
+ i sin
= ei 3
3
3

) z = sin

+ i cos
6
6

I . sin + i cos = i (cos i sin ) = i (cos () + i sin ())

= ei 2 ei() = ei( 2 )

+ i cos = ei( 2 6 )
6
6

|z| = 1, =
3
!

+ i sin
z = cos
3

sin

= ei 3

II . , ,
.

1
3

sin + i cos = + i
6
6 2
2

|z| = 1, = arctg 2 = arctg 3 =


3
1
2
!
!

+ i sin
= ei 3
z = cos
3
3

) z = 2ei 3

, 1 = ei :

2ei 3 = ei 2ei 3 = 2ei( 3 ) = 2ei 3


2
|z| = 2, =
3
!
!!
2
2
z = 2 cos
+ i sin
3
3

19. :
) (1 + i)n
 n n  n

2 ei 4 =
2
(1 + i) = 2ei 4 (1 + i)n =

cos

!
n
+ i sin
4

!!
n
4

n
) 1 i 3


n

2n
i 2
3
1 i 3 = 2n ei 3 = 2n
1 i 3 = 2e

1 i tg
1 + i tg

!
!!
2n
2n
cos
+ i sin
3
3

!n

cos i sin
sin
!
!

1 i cos
cos

i
sin

ei
1 i tg
cos
=
=
=
=
= ei2

1 + i tg
cos + i sin
ei
sin cos + i sin
1+i
cos
cos
!n
1 i tg
= ei2n = (cos (2n) + i sin (2n))

1 + i tg
) (1 + cos + i sin )n
:
1 + cos + i sin = ei0 + ei = cos 0 + i sin 0 + cos + i sin = cos 0 + cos + i (sin 0 + i sin ) =
!
!
!

= 2 cos cos + i 2 sin cos


= 2 cos2 + i sin cos
= 2 cos
cos + i sin
2
2
2
2
2
2
2
2
2
2
(2 cos 2 , , ). :
!n
!
!n
n

n
n
cos
= 2 cos
ei 2
(1 + cos + i sin )n = 2 cos
+ i sin
2
2
2
2
) (1 cos + i sin )n
:
1 cos + i sin = 1 (cos i sin ) = 1 (cos () + i sin ()) = ei0 ei =

= cos 0 + i sin 0 cos () i sin () = cos 0 cos () + i (sin 0 sin ()) =


!
!
!
!!

= 2 sin
sin + i 2 sin cos
= 2 sin
sin
+ i cos
=
2
2
2
2
2
2
2
!
!!

= 2i sin
cos
+ i sin
= 2 sin ei 2 e 2 = 2 sin ei( 2 )
2
2
2
2
2
:
n

(1 cos + i sin ) =

2 sin
2

!n
)
i(
2

2 sin
2

!n
cos

( )n
2

!
+ i sin

!!
( )n
2

4
1
z = 1,

1=

2k
0
4
1ei( 4 + 4 )

|z| = 1,

=0
i0
e =1

ei 2 = i
(k = 0, 1, 2, 3)
ei = 1

i 3
e 2 = i
={z}

i
1

<{z}

1
z = 1,

2k
4
4
1 = 1ei( 4 + 4 )

|z| = 1,

i
2
2
4 =
e
+
i

2 2

i 3

e 4 = 22 + 22 i

(k = 0, 1, 2, 3)
2
2
i 5

4 =
e

2 2
i 7
2
2
e 4 = 2 2i

={z}

<{z}

3
1
|z| = 1,

z = 1,

1=

1ei( 3 +

2k
)
3


3
1
i3

=
+
i
e

2
2
i
(k = 0, 1, 2) e = 1

i 53
e = 12 23 i
={z}

i
1

<{z}

4
1 + i 3
z = 2,

|z| = 1,

2
3

2
2k

k
4
4
1 + i 3 = 2ei( 34 + 4 ) = 1, 0905ei( 6 + 2 ) (k = 0, 1, 2, 3)

3
i 6
1,
0905e
=
1,
0905(
+ 12 i)

2
1, 0905ei 3 = 1, 0905( 1 + 3 i)
2
2

3
i 7

6
1, 0905e = 1, 0905( 2 12 i)

5
1, 0905ei 3 = 1, 0905( 21 23 i)

={z}

<{z}

1
|z| = 1,

z = 1,

1=

1ei( 8 +

2k
)
8

=0

ei0 = 1

2
2
i 4

e
=
+
i

2
2

e 2 =i

ei 34 = 2 + 2 i
2
2
(k = 0, 1, 2, . . . , 7)
i

e
=
1

ei 4 = 22 22 i

ei 2 = i

i 74
e = 22 22 i
={z}

<{z}

20.
21. sin x cos x
) sin 4x, cos 4x:
10

(cos 4x + i sin 4x) = ei4x = (eix )4 = (cos x + i sin x)4 =


= cos4 x + 4 cos3 xi sin x 6 cos2 x sin2 x 4 cos xi sin3 x + sin4 x
cos 4x = cos4 x 6 cos2 x sin2 x + sin4 x
sin 4x = 4 cos3 x sin x 4 cos x sin3 x
) sin 5x, cos 5x:
(cos 5x + i sin 5x) = ei5x = (eix )5 = (cos x + i sin x)5 =
= cos5 x + 5 cos4 xi sin x 10 cos3 x sin2 x 10 cos2 xi sin3 x + 5 cos x sin4 x + i sin5 x
cos 5x = cos5 x 10 cos3 x sin2 x + 5 cos x sin4 x
sin 5x = 5 cos4 x sin x 10 cos2 x sin3 x + sin5 x

22. , x, :
) sin4 x:
sin4 x =

eix eix
2i

!4
=


1  i4x
e 4ei3x eix + 6ei2x ei2x 4eix ei3x + ei4x =
16



1  i4x
1
[2 cos 4x 8 cos 2x + 6]
e + ei4x 4ei2x + 4ei2x + 6 =
16
16

) cos4 x:
4

cos x =

eix + eix
2

!4
=


1  i4x
e + 4ei3x eix + 6ei2x ei2x + 4eix ei3x + ei4x
16


1  i4x
1
1
3
1
e + ei4x + 4ei2x + 4ei2x + 6 =
[2 cos 4x + 8 cos 2x + 6] = cos 4x + cos 2x +
16
16
8
2
8

) sin5 x:
) cos5 x:

cos5 x =

eix + eix
2

!5
=


1  i5x
e + 5ei4x eix + 10ei3x ei2x + 10ei2x ei3x + 5eix ei4x + ei5x =
32


1  i5x
1
e + ei5x + 5ei3x + 5ei3x + 10eix + 10eix =
[2 cos 5x + 10 cos 3x + 20 cos x] =
32
32
1
5
5
cos 5x + cos 3x + cos x
=
16
16
8

11

23. , z n-
a, z :
z n = a (a R) (z)n = a
C : z z z . . .z = a. (z)n = z z . . .z = z z z . . . z (
) = z n = a = a ( a ). B
24. , n- z n- z
:

z=

n
z

C b n z, (b)n = z (bn ) = z bn = z b n z.

, , n z n z . B

2n
25. , n z n z
z2:

2n
2n
z 2 : a n z an = z a2n = z 2 a
z2.
C , n z

2n
2n
, n z
z 2 : a n z an = z a2n = z 2 a
z2.

2n
2n
, n z n z z 2 . n z n z n ,
z 2 2n .

2n
2

z n z n z,

an = z = z, . ,

2n
n
z 2 = n z z B
26. :

) n z n w = z n w

n
C a n z n w, an = z n w azn = w ( az )n = w az n w a z n w. ,

n
z n w z n w, , , . B

) n z n w = z n w
p

I) n : 2 1 = 2 (12 )1 6= 1 2 1.
p

II) n : n z n w = n (z)n w = z n w ( ) ).

) n zw = u n w, u n z.

C , un = z, , n zw , n un w = u n w (
12

) ). B

nk
27.
z k = n z?

nk

z k nk , n z n , ,
k, 1.
28. n- 1
n- , ,
i0

2
n

4
n

(n1)2
n

0+ 2
+ 4
+...+
n
n

e e e ...e
= e
n 1 .

(n1)2
n

i(

= e

0+

(n1)2
n
2

n)

= ei(n1) . 1

29. n- 1
1 + 2 + 3 + . . . + n1 = 0
n .
n - .
0, ,
2/k , - 2/k,
, .
: 1 , 2 , 3 , . . . , n1 z n 1 = 0 C, 1 + 2 + 3 + . . . + n1 = a1 . a1 = 0, ,
n- 1 0.
32. ,
:
) (A + B)2 = A2 + 2AB + B 2
) (A + B)(A B) = A2 B 2
) (A + B)2 = (A + B)(A + B) = A2 + AB + BA + B 2 .
) (A + B)(A B) = A2 AB + BA B 2 .
, AB = BA, .
34.

Df. ,
: en = 1 e1 + 2 e2 + . . . + m em .
, ,
, .
, .. ,
13

,
, .
) , e1 ; e2 ; . . . ; en .
en+1 . -
?
, .
) , e1 ; e2 ; . . . ; en .
en+1 . -
?
, , .
) , e1 ; e2 ; . . . ; en . en .
- ?
, , .
) , e1 ; e2 ; . . . ; en . en .
- ?
,
.
35. :
) (1)x = x
)
)
) 0x = 0
) 0 = 0
) x = 0 = 0 x = 0
)

14

Вам также может понравиться